CHALLENGES AND PROBLEMS FACED IN TEACHING MATHEMATICS - Dr. Sonu Bansal (Innovative Research Thoughts, 2022)
As it is crucial for a person to live a better life, Mathematics has a special position in the educational curriculum. However, it is well known that the majority of kids find mathematics challenging. This study investigates the challenges teachers and students in high school perceive when learning and teaching mathematics. Fourteen maths teachers and 200 ninth grade pupils took part in the poll. Both close and open ended questions are included in the questionnaires on how students and teachers are perceived. The study took into account cognitive, emotional, and contextual factors that affect learning mathematics. The factors that make mathematics difficult for students to learn included difficulty in remembering the content learned in the previous classes, rapid forgetting of the learned material and the difficulty in understanding mathematics concepts. Further analysis revealed that students who feel mathematics highly difficult tends to believe that they lack in learning strategies. Such students have lack of self efficacy and feel more difficulty in understanding mathematics. Students who feel Mathematics as highly difficult tends to forget it faster. Conversely students who feel mathematics as fairly easy report their teachers teaching them well and understanding the concepts quickly. It was noted that the students who feel Mathematics as highly difficult tends to leave the task with little effort than those who feel the subject easy. Teachers cite prerequisites and students' lack of effort as the main causes of mathematics being a challenging subject for students. It was also believed that pupils' lack of enthusiasm, unwillingness to ask for assistance, and inattentiveness in class contributed to the challenge of learning mathematics. Additionally, teachers stated that it is challenging to teach mathematics due to the lack of necessary prerequisites, the difficulty of children quickly learning the ideas, and the increased number of students in a classroom. The results show that teachers must understand the value of making classroom mathematics engaging so that pupils will put forth the effort necessary to acquire it. The outcome is discussed in light of the students' perspectives and learning methods.